Surface modification of polypropylene waste by the radiation grafting of styrene and upcycling into a cation‐exchange resin. Issue 10 (25th November 2018) - Hassan, Muhammad Inaam ul; Taimur, Shaista; Khan, Ijaz Ahmed; Yasin, Tariq; Ali, Syed Wasim
ABSTRACT: In this study, we radiation‐grafted polypropylene waste (PPw) powder obtained from the accelerated aging of pristine polypropylene with styrene (St) using γ rays from a Co‐60 source at dose rate of 4.78 kGy/h. The influence of the variation of the γ absorbed dose, solvent types, and monomer concentration on the grafting yield was investigated. Solution grafting in methanol resulted in a higher grafting yield of 162.6% at 30 kGy in contrast to the 69.5% obtained in the absence of solvent. Grafting was found to be enhanced with the increased dilution of St with methanol. The grafted St units were incorporated with sulfonic (SO3 H) groups by a sulfonation reaction with sulfuric acid. Fourier transform infrared spectroscopy, X‐ray diffraction spectrometry, scanning electron microscopy/energy‐dispersive X‐ray spectroscopy, and thermogravimetric analysis were used to characterize the grafted and sulfonated products. Sulfonation of 162.6% grafted PPw powder exhibited a maximum ion‐exchange capacity (IEC) of 3.56 mequiv/g. The utilization of PPw and its conversion into sulfonated PPw with comparable IECs is a new addition to already existing radiation grafting systems. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47145. Abstract :